2016
DOI: 10.1038/ejcn.2016.234
|View full text |Cite
|
Sign up to set email alerts
|

The effects of policy actions to improve population dietary patterns and prevent diet-related non-communicable diseases: scoping review

Abstract: Poor diet generates a bigger non-communicable disease (NCD) burden than tobacco, alcohol and physical inactivity combined. We reviewed the potential effectiveness of policy actions to improve healthy food consumption and thus prevent NCDs. This scoping review focused on systematic and non-systematic reviews and categorised data using a seven-part framework: price, promotion, provision, composition, labelling, supply chain, trade/investment and multi-component interventions. We screened 1805 candidate publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 60 publications
(101 reference statements)
1
103
1
1
Order By: Relevance
“…It is acknowledged that the effect of nutrition education as such is modest and usually decreases over time. In contrast, governmental pricing interventions making healthy foods more affordable than unhealthy foods appear consistently powerful in promoting healthy eating habits (Hyseni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that the effect of nutrition education as such is modest and usually decreases over time. In contrast, governmental pricing interventions making healthy foods more affordable than unhealthy foods appear consistently powerful in promoting healthy eating habits (Hyseni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to examine the consistency of our findings, we compared our results to other studies which used disparate approaches on examining the impacts of food policy implementation such as tax or subsidy on food consumption patterns [37][38][39]. These studies found that the government policy have an influence on change in the consumption patterns for particular foods.…”
Section: Verification Of Modeling Approachmentioning
confidence: 71%
“…Darmon et al [37] and Hyseni et al [38] particularly found the evidence that pricing mechanism (price intervention) on increase and decrease in prices of unhealthy and healthy foods through taxes and subsidies can change food consumption patterns and improve the nutritional quality of diets. Miller and Cassady [39] investigated the impact of providing additional nutrition information on healthy dietary intake promotion.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Nesse contexto os hábitos alimentares desadequados assumem um papel relevante enquanto principal fator de risco evitável. De acordo com a literatura, 17 as estratégias de alteração de hábitos alimentares por parte das populações devem ser transversais a diferentes áreas e abordagens, das quais se destacam a educação para a saúde, promoção da literacia, e as que visam alterações do ambiente alimentar e que podem ir desde a autorregulação (i.e. redução do sal no pão) a uma utilização inteligente da fiscalidade.…”
Section: Perspetivas Futurasunclassified